IMPLEMENTATION SIMPLE ADDITIVE WEIGHTING METHOD IN DETERMINING FEASIBILITY SACRIFICIAL ANIMALS - Saputro, Nugroho Dwi; Waliyansyah, Rahmat Robi; Novita, Mega (Jurusan Teknologi Informasi Universitas Semarang, 2022)
Many things from the life sector have used the existence of technology. Where a technology is able to help various problems in various fields such as livestock and agriculture. Computers have been included in it as a tool to do a job or identify existing problems. However, sometimes as a practitioner in the field of animal husbandry, especially qurban animals, they come to the conclusion that it is often found that sacrificial animals in the market that want to be sacrificed do not meet the requirements both in syari ah (law) and health. With the application of determining the feasibility of sacrificial animals according to the Syariah using the web-based Simple Additive Weighting (SAW) method. This system is later expected to be able to determine whether or not a sacrificial animal will be sacrificed so that the community or people who sacrifice are not harmed and the reward for the sacrifice is perfect.